2014
DOI: 10.1155/2014/142828
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral Characterization, and Antiproliferative Studies of Mixed Ligand Titanium Complexes of Adamantylamine

Abstract: Titanium complexes have been synthesized by the reaction between titanium tetrachloride (TiCl4), respective bidentate ligand [4,4′ -dimethoxy-2,2′ -bipyridine (bpome), 6,6′-dimethyl-2,2′-bipyridine (dpme), 1,2-diaminocyclohexane (dach), 1,10-phenanthroline (phen), and benzoylacetone (bzac)], and adamantylamine (ada) in 1 : 2 : 2 molar ratios, respectively. The structure of synthesized complexes was confirmed using elemental analysis, FTIR, UV-visible, 1H NMR, and mass spectrometry techniques. The nanocrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…They have also been reported as being biologically active against pathogenic microorganisms [ 11 – 13 ]. Metal complexes containing different ligands with oxygen and sulfur donor atoms have been reported in the literature, and among these highlights are the dithiocarbamates and β -diketones mixed ligand complexes [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have also been reported as being biologically active against pathogenic microorganisms [ 11 – 13 ]. Metal complexes containing different ligands with oxygen and sulfur donor atoms have been reported in the literature, and among these highlights are the dithiocarbamates and β -diketones mixed ligand complexes [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic activity of the synthesized complexes against the HeLa, C6, and CHO cell lines was determined using the colorimetric 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. This assay was carried out in triplicate in 96 well plates [ 15 , 16 ]. Briefly, the cell pellet was resuspended in complete growth medium to get 1.5 × 10 5 cells/mL and 100 μ L of cell suspension per well were seeded in tissue culture plate.…”
Section: Methodsmentioning
confidence: 99%
“…The titanium complexes were synthesized by reacting titanium tetrachloride and nitrogen containing ligands in predetermined molar ratios. However, the detailed synthetic procedure and chemicals used for the synthesis of titanium complexes have been previously reported [ 15 17 ]. The proposed chemical structure of titanium complexes which were used for DNA binding studies has been shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, platinum, titanium and zinc complexes with adamantylamine ligand were synthesized, characterized and studied from the perspectives of therapy and biological interest. [12][13][14][15] For example, platinum(IV) complexes with adamantylamine were thoroughly tested for their biological activity and have the potential to provide a significantly improved therapy for many types of tumors. 13 To the best of our knowledge, a complex of 1-adamantanamine with silver(I) has not been described, although some similar compounds could be found in the literature.…”
mentioning
confidence: 99%